The investigation of the responses to phytohemagglutinin in the patients of non-hodgkin’s lymphoma who were candidates for high dose chemotherapy, autologous bone marrow, or peripheral stem cell transplantation (Annals of Medical Research, 2021)
None
Keywords: s : Non-Hodgkin lymphoma, PHA response, bone marrow, peripheral stem cell, transplantation